Nanotherapy for Cancer and Biological Activities of Green Synthesized AgNPs Using Aqueous Saussurea costus Leaves and Roots Extracts - Mina A. Almayouf; Raihane Charguia; Manal A. Awad; Abir Ben Bacha; Imen Ben Abdelmalek (MDPI AG, 2024)
Background/Objectives: Nanoparticles derived from medicinal plants are gaining attention for their diverse biological activities and potential therapeutic applications. Methods: This study explored the antioxidant, anti-inflammatory, anti-tumoral, and antimicrobial properties of green synthesized silver nanoparticles (AgNPs) using the aqueous leaf and root extracts of Saussurea costus (S. costus). The physicochemical characterizations of both biosynthesized AgNPs using the aqueous leaf extract (L-AgNPs) and root extract (R-AgNPs) were examined using UV spectroscopy, fluorescence spectroscopy, transmission electron microscopy, energy-dispersive X-ray spectroscopy, X-ray diffraction, dynamic light scattering, and Fourier-transform infrared spectroscopy. The antioxidant activity measured using ABTS, DPPH, and FRAP assays showed that AgNPs, particularly from roots, had higher activity than aqueous extracts, attributed to phenolic compounds acting as capping and antioxidant agents. Results: Enzyme inhibition studies indicated that AgNPs exhibited remarkable anti-inflammatory effects, inhibiting COX-1, 5-LOX, and secreted PLA2 enzymes by over 99% at 120 µg/mL, comparable to standard drugs. The anti-tumoral effects were evaluated on the human cancer cell lines HCT-116, LoVo, and MDA-MB-231, with AgNPs inhibiting cell proliferation dose-dependently and IC50 values between 42 and 60 µg/mL, demonstrating greater potency than extracts. The AgNPs also showed enhanced antimicrobial activities against various microbial strains, with IC50 values as low as 14 µg/mL, which could be linked to nanoparticle interactions with microbial cell membranes, causing structural damage and cell death. Conclusions: These findings suggest that S. costus-derived AgNPs are promising natural, biodegradable agents for various biological applications and potential new therapeutic agents, necessitating further research to explore their mechanisms and applications.